STRATEGY AND PRACTICE OF SOCIAL AND ECONOMIC REFORMS IN THE RUSSIAN FEDERATION AND THE PEOPLE'S REPUBLIC OF CHINA AT THE END OF 20 - THE BEGINNING OF THE 21ST CENTURIES: SIMILARITY AND DIFFERENCES - Y. Shmelev (Publishing House of the State University of Management, 2016)
The comparative analysis of strategy and practice of social and economic reforms in Russia and China for the last 30 years is carried out. Basic distinction as in setting of the goals of reforms, and strategy and practice of their realization is detected. It is established that both on concrete economic achievements, and from the point of view of viability of the chosen model of economic development of society China much more surpasses Russia. Experience of modernization of China can be useful to more effective and socially oriented reforming of Russia.